The Effect Of Free Cash Flow And Good Corporate Governance On Firm Value - Bertasari, Meilani; Susanto, Heri; Marnilin, Feni (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
The purpose of the study was to determine the condition of Free Cash Flow, Audit Committee, Managerial Ownership, and Institutional Ownership simultaneously on Company Value in food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2022. The research method uses qualitative research. Collection techniques with documentation methods obtained from internet information. Data analysis using multicollinearity, Multiple Linear Regression, Heteroscedasticity, Autocorrelation Test.  Based on the results of data analysis, it can be concluded that the highest Free Cash Flow value is owned by MLBI, and the lowest is owned by CLEO. The highest Audit Committee value is owned by BUDI, CAMP, CEKA, CLEO, DLTA, ICBP, INDF, MLBI, MYOR, ROTI, and STTP, and the lowest is owned by ULTJ. The value of Managerial Ownership is owned by CEKA, and the lowest is owned by TBLA. The highest Institutional Ownership value is owned by BUDI, CAMP, CEKA, CLEO, DLTA, ICBP, INDF, MLBI, MYOR, ROTI, and STTP, and the lowest is owned by ULTJ. The highest PBV value is owned by GOOD, and the lowest is owned by PT SKBM. Free Cash Flow, Audit Committee, Managerial Ownership, and Institutional Ownership simultaneously affect Firm Value. Keywords: Free Cash Flow, Good Corporate Governance, Audit Committee, Managerial Ownership, Institutional Ownership, firm value.